Association between the AUC0-24/MIC Ratio of Vancomycin and Its Clinical Effectiveness: A Systematic Review and Meta-Analysis - Men, Peng; Li, Hui-Bo; Zhai, Suo-Di; Zhao, Rong-Sheng (PLOS ONE, 2016)
Background A target AUC0-24/MIC ratio of 400 has been associated with its clinical success when treating Staphylococcus aureus infections but is not currently supported by state-of-the-art evidence-based research. Objective This current systematic review aimed to evaluate the available evidence for the association between the AUC0-24/MIC ratio of vancomycin and its clinical effectiveness on hospitalized patients and to confirm the existing target value of 400. Methods PubMed, Embase, Web of Sciences, the Cochrane Library and two Chinese literature databases (CNKI, CBM) were systematically searched. Manual searching was also applied. Both RCTs and observational studies comparing the clinical outcomes of high AUC0-24/MIC groups versus low AUC0-24/MIC groups were eligible. Two reviewers independently extracted the data. The primary outcomes were mortality and infection treatment failure. Risk ratios (RRs) with 95% confidence intervals (95%CIs) were calculated. Results No RCTs were retrieved. Nine cohort studies were included in the meta-analysis. Mortality rates were significantly lower in high AUC0-24/MIC groups (RR = 0.47, 95%CI = 0.31–0.70, p<0.001). The rates of infection treatment failure were also significantly lower in high AUC/MIC groups and were consistent after correcting for heterogeneity (RR = 0.39, 95%CI = 0.28–0.55, p = 0.001). Subgroup analyses showed that results were consistent whether MIC values were determined by broth microdilution (BMD) method or Etest method. In studies using the BMD method, breakpoints of AUC0-24/MIC all fell within 85% to 115% of 400. Conclusions This meta-analysis demonstrated that achieving a high AUC0-24/MIC of vancomycin could significantly decrease mortality rates by 53% and rates of infection treatment failure by 61%, with 400 being a reasonable target.